Decentring Criminal Law : Understandings of Justice by Victim-Survivors of Sexual Violence and their Implications for Different Justice Strategies - Antonsdottir, Hildur Fjola (Lund University, 2020)
The compilation dissertation is shaped by the ambition of Critical Theory, which is to imagine an alternative and emancipatory political reality to the status quo, where people who have been subjected to sexual violence are recognised and enjoy parity of participation in social life. More specifically, it aims to understand how victim-survivors of sexual violence in Iceland perceive, experience, and understand justice; and how, in a Nordic socio-legal context, this knowledge can be used to expand and develop strategies which are capable of meeting the justice interests of victim-survivors within and outside of the criminal justice system. The dissertation contributes to a broad survivor-centred justice agenda which entails the decentring of criminal law in the imaginary space of justice.Paper I analyses how Danish and Norwegian legal policy documents represent the “problem” of victims’ legal status and rights, and the assumptions underpinning arguments for and against strengthening victims’ rights. Paper II explores how victim-survivors experience the criminal justice process in Iceland. Paper III analyses victim-survivors’ experiences of different non-traditional, formal and informal, justice mechanisms and practices in Iceland. Paper IV examines victim-survivors’ views on civil tort claims and monetary compensation in Iceland.In the context of Nordic legal policies, the study shows that the status and rights of victims in the criminal justice procedure are subject to different interpretations of legal principles, which opens up the question of procedural justice to principles of social justice. In line with principles of social justice, being assigned the legal status of a witness in the criminal case with limited procedural rights is understood as a form of injustice by survivors. While the meaning of justice is comprised of several factors, the study highlights how experiences of justice can be connected to notions of space and the ability to exercise one’s freedoms. In the context of tort law, the study ...